Visualising Energy Use for Smart Homes and Informed Users. (November 2015) - Stinson, Jon; Willis, Alexandra; Williamson, Julio Bros; Currie, John; Smith, R.Sean
Abstract: We evaluate the changes to domestic electricity and gas consumption when the occupants have local access to a coloured real time in-home display (IHD). We report the preliminary six months findings of a three year research project involving 52 new build Scottish dwellings (flats and houses). On average, when compared to households with no IHD (n=22) the households with the IHD (n=30) reduced their gas and electricity consumption by 20% and 7% respectively. We found that the IHD was valued by the users for its ability to incite behaviour to reduce gas consumption and reinforce existing electricity saving behaviour.